THE INFLUENCE OF CURRENT RATIO, DEBT TO ASSETS RATIO, AND DEBT TO EQUITY RATIO ON RETURN ON ASSETS AT PT UNILEVER INDONESIA Tbk - Dewi, Nadira Aulia Setia; Herlinawati, Erna (Universitas Muhammadiyah Tangerang, 2025)
This study aims to determine the effect of the Current Ratio (CR), Debt to Assets Ratio (DAR), and Debt to Equity Ratio (DER) on Return On Assets (ROA) at PT Unilever Indonesia Tbk during the period 2014-2023. This research is motivated by the challenges faced by the company, including the impact of the COVID-19 pandemic and the potential for boycotts. The research method used is quantitative with a descriptive and verificative approach. Data were taken from the company's annual financial statements and analyzed using IBM SPSS 26. The research results show that partially, CR and DAR do not have a significant effect on ROA, while DER has a significant negative effect on ROA. Simultaneously, CR, DAR, and DER have a significant effect on ROA. The coefficient of determination of 95.5% indicates that the variables CR, DAR, and DER explain most of the variability in ROA, with 4.1% influenced by other factors.